2014
DOI: 10.4062/biomolther.2013.095
|View full text |Cite
|
Sign up to set email alerts
|

Methyl p-Hydroxycinnamate Suppresses Lipopolysaccharide-Induced Inflammatory Responses through Akt Phosphorylation in RAW264.7 Cells

Abstract: Derivatives of caffeic acid have been reported to possess diverse pharmacological properties such as anti-inflammatory, anti-tumor, and neuroprotective effects. However, the biological activity of methyl p-hydroxycinnamate, an ester derivative of caffeic acid, has not been clearly demonstrated. This study aimed to elucidate the anti-inflammatory mechanism of methyl p-hydroxycinnamate in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells. Methyl p-hydroxycinnamate significantly inhibited LPS-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…We propose that such results might reflect the reasons of delaying inflammation reaction which lead to further deterioration effects on wound. The present results agreed with those reported by Choi et al and Vo et al [25], they found that inflammation occurs due to stimulation of NF-κB, iNOS, and COX-2; therefore, inhibited activation of these pro-inflammatory mediators have attenuated adverse inflammation related illness.…”
Section: Discussionsupporting
confidence: 93%
“…We propose that such results might reflect the reasons of delaying inflammation reaction which lead to further deterioration effects on wound. The present results agreed with those reported by Choi et al and Vo et al [25], they found that inflammation occurs due to stimulation of NF-κB, iNOS, and COX-2; therefore, inhibited activation of these pro-inflammatory mediators have attenuated adverse inflammation related illness.…”
Section: Discussionsupporting
confidence: 93%
“…Plates were then washed fourteen times and incubated with substrate solution for 15 min at room temperature. Stop solution was then added and absorbance was read at 450 nm ( Vo et al ., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study showed that apocynin attenuated LPS‐induced IκB degradation in a concentration‐dependent manner preventing nuclear translocation of NF‐κB. Suppression of NF‐κB transcription mediated anti‐inflammatory properties of natural products against LPS‐induced inflammation in RAW264.7 cells [Vo et al, ]. However, further studies are necessary to clearly delineate the exact mechanism by which apocynin leads to the suppression of iNOS and COX‐2 expression.…”
Section: Discussionmentioning
confidence: 73%
“…Other signaling pathways such as PI3K/Akt may also be involved in LPS‐induced pro‐inflammatory responses [Ha et al, ]. Activation of Akt signaling pathway suppressed LPS‐induced inflammatory gene expressions and cytokine secretion [Vo et al, ], suggesting that multiple signaling pathways are involved in LPS‐induced inflammatory processes. Therefore, further studies are necessary to further understand the contribution of other signaling pathways to LPS‐induced inflammatory events.…”
Section: Discussionmentioning
confidence: 99%